Varietal richness of grapevine (Vitis vinifera L.) from the Majes Valley, Peru: Identification, morphological characterization, ampelographic and genetic analysis - Bardales, Roxana (2022)
The “Majes Valley” in the province of Castilla – Arequipa Region, with a tradition in the production of wine and pisco, from grapevines introduced in the mid-sixteenth century, which are still preserved by some producers, with little knowledge of the varietal richness they possess, generating confusion in the identification of varieties and devaluing their winegrower potential. In this work, a varietal survey was carried out by wine-growing areas, characterizing the local varieties of old vineyards, with 14 primary descriptors recommended by the OIV-2009 and genetically identifying a sample of 11 phenotypes with the use of 9-SSR molecular markers when compared in the VIVC international database record. Seven wine-growing areas of the valley and 39 varieties with local names were identified, initially forming 13 groups of different names, which when analyzed by means of the canonical discriminant analysis and of main components, high inter- and intra-group phenotypic variability is evidenced due to the influence of some characters. In the analysis of the berry color the blue-black coloration predominates. Four varieties registered in the VIVC were genetically identified, corresponding to ´Listan Prieto` (syn. Negra Criolla and Moscatel), ´Quebranta` (syn.Vinera), ´Muscat Hamburg` (syn.Italia Negra) and ´Jacquez` (syn. Borgoña Majeña) and 2 unregistered varieties “Cantarita” and “Aceituna de Cotahuasi”. A varietal diversity with characteristics of interest in viticulture and plant breeding is observed, with contribution to the varietal identity of known and new creole varieties, contributing to the heritage value of the vine.